Between the West and Asia: "Humanistic" Japanese Family Planning in the Cold War. Issue 4 (1st December 2016) - Homei, Aya
Abstract : This article studies the formation of Japanese ventures in family planning deployed in various villages in Asia from the 1960s onward in the name of development aid. By critically examining how Asia became the priority area for Japan's international cooperation in family planning and by analyzing how the adjective humanistic was used to underscore the originality of Japan's family planning program overseas, the article shows that visions of Japanese actors were directly informed by Japan's delicate position in Cold War geopolitics, between the imagined West represented by the United States and "underdeveloped" Asia, at a time when Japan was striving to (re)establish its position in world politics and economics. Additionally, by highlighting subjectivities and intra-Asian networks centered on Japanese actors, the article also aims to destabilize the current historiography on population control, which has hitherto focused either on Western actors in the transnational population control movement or on non-Western "acceptors" subjected to the population control programs.